Isomorphic diffuse glioma is a morphologically and molecularly distinct tumour entity with recurrent gene fusions of MYBL1 or MYB and a benign disease course - Wefers, Annika K.; Stichel, Damian; Schrimpf, Daniel; Coras, Roland; Pages, Mélanie; Tauziède-Espariat, Arnault; Varlet, Pascale; Schwarz, Daniel; Söylemezoglu, Figen; Pohl, Ute; Pimentel, José; Meyer, Jochen; et al. (Acta neuropathologica, 2020)
The “isomorphic subtype of diffuse astrocytoma” was identified histologically in 2004 as a supratentorial, highly differentiated glioma with low cellularity, low proliferation and focal diffuse brain infiltration. Patients typically had seizures since childhood and all were operated on as adults. To define the position of these lesions among brain tumours, we histologically, molecularly and clinically analysed 26 histologically prototypical isomorphic diffuse gliomas.